2021
DOI: 10.3389/fcvm.2021.639222
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and COVID-19: Ongoing Controversies

Abstract: Coronavirus disease 2019 (COVID-19) has become a worldwide pandemic responsible for millions of deaths around the world. Hypertension has been identified as one of the most common comorbidities and risk factors for severity and adverse outcome in these patients. Recent investigations have raised the question whether hypertension represents a predictor of outcome in COVID-19 patients independently of other common comorbidities such as diabetes, obesity, other cardiovascular diseases, chronic kidney, liver, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 35 publications
2
43
0
1
Order By: Relevance
“…Interpretation of the data from the beginning of the pandemic, and partially confirmed later, revealed that the main risk factors for admission to intensive care with a fatal outcome were advanced age [ 6 ], male sex [ 7 ], smoking [ 8 ], obesity [ 9 , 10 ], hypertension [ 11 ], diabetes mellitus [ 12 , 13 , 14 , 15 ], lung disease [ 16 ], cancer [ 17 , 18 ], and cardiovascular disease [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of the data from the beginning of the pandemic, and partially confirmed later, revealed that the main risk factors for admission to intensive care with a fatal outcome were advanced age [ 6 ], male sex [ 7 ], smoking [ 8 ], obesity [ 9 , 10 ], hypertension [ 11 ], diabetes mellitus [ 12 , 13 , 14 , 15 ], lung disease [ 16 ], cancer [ 17 , 18 ], and cardiovascular disease [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…CCBs act through the relaxation of vascular smooth muscle cells, which results in vasodilation and thereby reduces blood pressure. Hypertension is a comorbidity often seen in severe COVID-19 disease and is linked to poor clinical outcomes in elderly populations [ 7 , 8 , 10 ]. The research discussed suggests there may be some benefit from the use of dihydropyridine CCB in the prevention of severe COVID-19 disease.…”
Section: Targeting Covid-19 Therapymentioning
confidence: 99%
“…While varying respiratory symptoms are the common clinical manifestations of disease, cardiovascular events, including myocarditis, arrhythmias, heart failure, and ischemic stroke, have been reported in multiple studies [ 6 , 7 ]. Similar to other respiratory infections, those with established cardiovascular disease (CVD) or its risk factors are at a higher risk for developing severe COVID-19, where disease onset can cause a further decline of cardiac pathologies as well as trigger acute onset of new cardiac complications [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension; a long-term medical condition in which the blood pressure in the arteries is persistently elevated, has been recognized as one of the most frequent comorbidities and risk factors for the seriousness and adverse consequences in COVID-19 patients [1] . Several drug classes have been used for the treatment of high blood pressure such as angiotensin converting enzyme (ACE)-inhibitors, diuretics, β-blockers, calcium channel blockers (CCBs) and others [2] .…”
Section: Introductionmentioning
confidence: 99%